PENYAJIAN LAPORAN KEUANGAN PEMERINTAH DESA (STUDI PADA PEMERINTAH DESA AMPELDENTO KABUPATEN MALANG) - Khilmiyah, Isniatul; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to find out the presentation of financial statement of Ampeldento village, Pakis Sub-district, Malang district in 2015 has been presented in accordance with the PERMENDAGRI No. 113 of 2014 about the Financial Management of the village.The research method has been carried out by using descriptive research method and qualitative approach. The data has been conducted by using primary and secondary data as the sources. The primary data has been obtained from the interview which is relevant to the presentation of financial statement. It has been found from the result of this research that the presentation of financial statement of Ampeldento village is based on the PERMENDAGRI No. 113 of 2014 which shows the accountable and transparent implementation which can be reviewed from the responsibility statement of village government budget (APBDesa), but when it is reviewed from the record it has not been completely in accordance with the prevailing regulations, therefore further training and development is required. The primary constraint is the low competency of the human resources and the ineffectiveness of the training of village apparaturs, therefore continuous special attention and seriousness from the local apparaturs is required.Keywords: Presentation of village financial statement, human resources, villagegovernment budget, accountable and transparent.